1981
DOI: 10.1111/1523-1747.ep12482488
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infections in Rabbits and Humans with Pityrosporum orbiculare and P. ovale

Abstract: The purpose of this investigation was to produce experimental tinea versicolor in rabbits and humans with Pityrosporum orbiculare and P. ovale. P. orbiculare and P. ovale were inoculated, with and without occlusion, on the inside of the ear in 10 male rabbits and on the upper arm in 10 patients with a history of tinea versicolor, and in 3 healthy volunteers. After 1 week tinea versicolor-like lesions were produced with both P. orbiculare and P. ovale in 8 of 10 rabbits. Likewise experimental infections, simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The name he gave the organism, P. orbicualre, is based primarily on the micromorphology. However, later studies have shown that the round and oval forms of the organism are not stable (12) and that the two forms can change from one to the other on special culture media or under special culture condi-tions (128) and when experimental infections are induced in rabbits (34).…”
Section: Malasseziamentioning
confidence: 99%
“…The name he gave the organism, P. orbicualre, is based primarily on the micromorphology. However, later studies have shown that the round and oval forms of the organism are not stable (12) and that the two forms can change from one to the other on special culture media or under special culture condi-tions (128) and when experimental infections are induced in rabbits (34).…”
Section: Malasseziamentioning
confidence: 99%
“…Experimental pityriasis (tinea) versicolor-like lesions have been produced with Pityrosporum orbiculare (P. ovale) under plastic occlusion in both rabbits and humans (1,5). A method for the in vitro estimation of the MICs of potential therapeutic agents against P. orbiculare (P. ovale) has also been described (2,4).…”
mentioning
confidence: 99%
“…The details of the experimental infections have been described previously (1,5). P. orbiculare ATCC 44031 was used.…”
mentioning
confidence: 99%
“…4 In the past, all were thought to be distinct fungi, but recent evidence suggests the three are variants of each other. 5,6 Tinea versicolor has a higher incidence in tropical climates and during warmer months in temperate climates than is seen in cooler environments.…”
Section: Discussionmentioning
confidence: 99%